Strategi Adaptasi Pedagang Pasar Tradisional Terhadap Persaingan Dengan Pasar Modern Di Kota Palembang - Faturochman, Faturochman; Saputra, Naufal Riandra; Raditian, Raditian; Panorama, Maya (VALUE, 2025)
This study aims to examine the adaptation strategies implemented by the Palembang city government to sustain the presence of traditional markets in the digital era. A descriptive qualitative approach was employed to analyze various policies and programs through document review and field observation. The findings reveal that digital transformation is the main focus, with traders being encouraged to utilize technologies such as live selling, online platforms, and digital payment systems. In addition, other strategies are implemented, including service quality improvement, product diversification, and maintaining market cleanliness and comfort. The government and market managers also provide training and assistance to help traders adapt to new technologies. However, the adaptation process faces several challenges, such as limited human resources, high initial investment costs, and the need for continuous education. The study concludes that well-planned adaptation strategies and consistent government support are essential to ensure that traditional markets remain relevant and can compete sustainably with modern markets.